Recent progress in terahertz sensors based on graphene metamaterials - Zesen Zhou; Zhilong Gan; Lei Cao (Discover Nano)
Abstract Graphene-based terahertz (THz) metamaterials (MMs) are at the forefront of high-sensitivity sensing, with applications spanning biochemical to environmental fields. This review examines recent advances in graphene MMs-based THz sensors, covering foundational theories and innovative designs, from complex patterns to graphene-dielectric and graphene-metal hybrids. We explore ultra-trace detection enabled by $$π$$ π - $$π$$ π stacking mechanisms, expanding capabilities beyond conventional refractive index-based methods. Despite significant theoretical progress, practical challenges remain due to material constraints; solutions such as multilayer graphene structures and hybrid low-mobility designs are discussed to enhance experimental feasibility. This review provides a comprehensive perspective on the evolving impact of graphene MMs, positioning them as transformative tools in multidisciplinary THz sensing.